2015
DOI: 10.1007/s10853-015-9553-4
|View full text |Cite
|
Sign up to set email alerts
|

Review on slip transmission criteria in experiments and crystal plasticity models

Abstract: A comprehensive overview is given of the literature on slip transmission criteria for grain boundaries in metals, with a focus on slip system and grain boundary orientation. Much of this extensive literature has been informed by experimental investigations. The use of geometric criteria in continuum crystal plasticity models is discussed. The theoretical framework of Gurtin (2008, J. Mech. Phys. Solids 56, p. 640) is reviewed for the single slip case. This highlights the connections to slip transmission criter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(75 citation statements)
references
References 123 publications
(187 reference statements)
0
74
0
1
Order By: Relevance
“…The heterogeneous deformation of polycrystals depends upon the local microstructure, where differences in grain orientations lead to different rates of deformation in each grain as constrained by the deformation of their neighboring grains (Delaire et al, 2000, Bieler et al, 2014. Deformation near grain boundaries mediates the strain jump and there is ample experimental evidence showing that grain boundaries may act as strong barriers for dislocations, which are stopped at the boundary leading to the formation of pile-ups, or are easily transferred to the neighbor grain leading to the propagation of deformation on a different slip system (Bieler et al, 2014;Bayerschen et al, 2016;Malyar et al, 2017;Hémery et al, 2018). Moreover, recent strain measurements by digital image correlation have shown that local strains near annealing twin boundaries may exceed several times the average strain (Stinville et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneous deformation of polycrystals depends upon the local microstructure, where differences in grain orientations lead to different rates of deformation in each grain as constrained by the deformation of their neighboring grains (Delaire et al, 2000, Bieler et al, 2014. Deformation near grain boundaries mediates the strain jump and there is ample experimental evidence showing that grain boundaries may act as strong barriers for dislocations, which are stopped at the boundary leading to the formation of pile-ups, or are easily transferred to the neighbor grain leading to the propagation of deformation on a different slip system (Bieler et al, 2014;Bayerschen et al, 2016;Malyar et al, 2017;Hémery et al, 2018). Moreover, recent strain measurements by digital image correlation have shown that local strains near annealing twin boundaries may exceed several times the average strain (Stinville et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From the above, there are at least two interdependent thresholds for slip transmission, one that is associated with a stress build up from a dislocation pileup for a given misorientation, and another that depends on magnitude of the slip system misalignment. Also, slip transmission is a subset of slip transfer, where transmission refers to passing a dislocation through a boundary; slip transfer could also occur by absorption of dislocations into a boundary, and emission of dislocations into the neighboring grain, a distinction that is discussed in greater depth in the review by Bayerschen et al (2016). As this distinction cannot be resolved in mesoscale observations, the term 'slip transfer' is used to be more general in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of polycrystals are controlled to a large extent by the boundaries between grains with different crystal orientations. Grain boundaries (GBs) usually lead to the formation of dislocation pile-ups, but sometimes they can absorb and re-emit dislocations, or dislocations pass through the boundary, as reviewed in [1]. These processes have a large influence on the yield strength, the nucleation of twins, the generation of cracks during fatigue and creep, etc., but reliable criteria to predict the dislocation/GB interactions are missing due to the complexity and variability of the GB structure.…”
mentioning
confidence: 99%
“…Due to the inter-grain interaction moduli, contained in the grain boundary Burgers tensor, the solution shows a slip transmission like characteristic, cf. discussion in [6].…”
Section: Discussion Of Resultsmentioning
confidence: 99%